Experiences of adults with cystic fibrosis in adhering to medication regimens: a qualitative systematic review. (May 2016) - Macdonald, Marilyn; Martin-Misener, Ruth; Helwig, Melissa; Smith, Lisa Janette; Godfrey, Christina M.; Curran, Janet; Murphy, Andrea
EXECUTIVE SUMMARY: Background: Adherence of adults with cystic fibrosis (CF) to medication regimens has been documented as problematic. Research related to adherence from the perspectives of adults with CF has been recommended for a further understanding of adherence. This review synthesized the qualitative evidence on adherence of adults with CF to medication regimens and should be of interest to healthcare providers. Review question: The question addressed in this review is, what are the experiences and perceptions of adults with CF and their adherence to a medication regimen? Types of participants : Adults with CF who are maintaining a medication regimen. Phenomenon of interest : The phenomenon of interest of this review is the experiences and perceptions of CF-affected adults who are taking prescribed medications to treat their CF and related conditions. Types of studies : This review included qualitative studies with the following designs: naturalistic inquiry, grounded theory, phenomenology and interpretive description. The gray literature was searched; however, no items were retained for the review. Search strategy: The search strategy used a three-step approach and was aimed at locating both published and unpublished studies. Key databases included, but were not limited to, CINAHL, PubMed and PsycINFO. The searches were not limited by date or language because we wanted to capture all existing qualitative studies related to the experiences and perceptions of adults following medication regimens. During the title and abstract screening, only English and French articles were included. Methodological quality: Qualitative studies triaged for appraisal were assessed by two Joanna Briggs Institute (JBI)-certified reviewers for methodological quality before inclusion. The reviewers used the JBI critical appraisal instruments, specifically the JBI Qualitative Assessment and Review Instrument (JBI-QARI). Data extraction: Data were independently extracted from the studies included in the review by two reviewers using the standardized data extraction tool from JBI-QARI. Data synthesis: Data were synthesized using the JBI process of meta-aggregation, identification of categories and development of a synthesized finding using the JBI-QARI software and methods. Results: Eight studies were included in the review. Twenty-two findings were aggregated into four categories culminating in one synthesized finding. The synthesis revealed that adults with CF carry both a physical and a psychosocial burden to adhere to medication regimens. Conclusion: Adults with CF carry a psychosocial burden to adhere to what healthcare providers expect, while trying to live a "normal" life. Consideration needs to be given to exploring with individuals what degree of adherence will assist them in maintaining health, yet be able to enjoy life.